Telehealth monitoring of a hypertensive elderly patient with the new VITASENIOR-MT system: a case study - Pereira, Telmo (2021)
Telehealth technologies providing remote monitoring of health parameters are a promising approach for the management of arterial hypertension in the elderly. The VITASENIOR-MT platform was developed as a telehealth solution designed to contribute to improve the health condition and quality of life, promoting safe and independent living of the old adult. It is an 'internet-of-things'-based solution relying on the interaction of the old adult with a TV-set to record biometric parameters and to receive warning and recommendations related to health and environmental sensor recordings. We present a pilot study with a male hypertensive patient, aged 81 years old, under anti-hypertensive treatment, with epilepsy, arthritis and paroxistic atrial fibrillation as major comorbidities. The VITASENIOR-MT was installed at the patient's assisted-dwelling house and a remote follow-up was implemented for 2 months, monitoring daily blood pressure and heart rate, as well as weight and indoor environmental parameters.